Cytologic diagnosis of vaginal metastasis from renal cell carcinoma: A case report - Queiroz, Conceição; Bacchi, Carlos Eduardo; Oliveira, Cassimiro; Carvalho, Marione; Santos, Délia Rabelo (Karger Publishers, 1999)
BACKGROUND: Metastasis of renal cell carcinoma to the vagina is rare, although it may be the first evidence of the existence of the primary tumor. CASE: A metastatic deposit of renal cell carcinoma in the vagina was diagnosed by cytology as clear cell adenocarcinoma, which was confirmed by biopsy. Radiographic and ultrasound examinations confirmed the renal site of origin, which was corroborated by immunohistochemistry of the biopsy specimen. CONCLUSION: When a cytologic diagnosis of vaginal clear cell adenocarcinoma is made, metastasis of renal cell carcinoma should be considered in the differential diagnosis.
Keywords: Carcinoma; Kidney neoplasms; Metastasis; Renal cell; Vaginal neoplasms; adult; case report; clinical feature; cytodiagnosis; cytopathology; diagnostic accuracy; differential diagnosis; female; human; kidney carcinoma; metastasis; priority journal; tumor biopsy; tumor localization; vagina carcinoma; Adenocarcinoma, Clear Cell; Biopsy; Carcinoma, Renal Cell; Cytodiagnosis; Diagnosis, Differential; Female; Humans; Immunohistochemistry; Kidney Neoplasms; Middle Aged; Vaginal Neoplasms